Estimasi Kebutuhan Tenaga Kerja Langsung Menggunakan Workload Analysis untuk Optimalisasi Beban Produksi - Syarifuddin, Rizal; Hayat, Encep Jianul; Sa’dudin Tjaptjani, Dedi (Jurnal Kalibrasi, 2025)
This study aims to identify the optimal number of workers in the production department of a fish-processing company using the Workload Analysis (WLA) method. This method is employed to calculate labor requirements based on the measurable workload at each work station. The WLA calculations show that the total number of workers needed is 22, while the company currently employs 29 workers, indicating a surplus of 7 workers. An analysis of labor productivity from July 2022 to June 2023 reveals fluctuations in efficiency, with the highest workload recorded in February (18.1160 m³/worker/day) and the lowest in November (15.9757 m³/worker/day). In addition, the study identifies several challenges in implementing WLA, including fluctuations in market demand, uncertainties in the production process, and limitations in the data required for accurate calculations. The study recommends that the company periodically adjust its workforce, enhance its data-collection systems, and account for market fluctuations as well as the adoption of new technologies in labor planning. The findings indicate that Workload Analysis (WLA) can support more rational decision-making regarding the appropriate number of workers for production lines. The presence of a surplus of seven workers and the observed variations in productivity across periods provide empirical evidence of operational efficiency dynamics within the fish-processing industry. One practical implication of this research is that workforce levels should be regularly revised, production data recording systems should be improved, and labor planning must be strengthened to adapt to technological advancements and changing market demand. This study makes a direct contribution to ongoing efforts to enhance sustainable productivity and manufacturing efficiency.